2023
DOI: 10.3389/fmars.2023.1193164
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of marine heatwaves in warming seas: the Mediterranean Sea case study

Abstract: Anomalous warming of the upper ocean is increasingly being observed in the Mediterranean Sea. Extreme events, known as marine heatwaves (MHWs), can have a profound impact on marine ecosystems, and their correct detection and characterization are crucial to define future impact scenarios. Here, we analyze MHWs observed over the last 41 years (1982–2022) in the Mediterranean sea surface temperatures (SSTs). We show that the intensification in frequency, intensity, and duration of Mediterranean MHWs in recent yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Likewise, a category III or Severe event corresponds to an anomaly 3 times greater than the difference and a category IV or Extreme event corresponds to an anomaly 4 times greater than the difference. Authors such as Martìnez et al (2023) suppressed the SST trend before applying the Hobday method for detecting MHWs. They consider that this suppression made it possible to use a fixed climatology without overestimating the properties of MHWs over time.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, a category III or Severe event corresponds to an anomaly 3 times greater than the difference and a category IV or Extreme event corresponds to an anomaly 4 times greater than the difference. Authors such as Martìnez et al (2023) suppressed the SST trend before applying the Hobday method for detecting MHWs. They consider that this suppression made it possible to use a fixed climatology without overestimating the properties of MHWs over time.…”
Section: Methodsmentioning
confidence: 99%
“…The 2022 Mediterranean MHW began in May and persisted through at least the end of the year (Martínez et al 2023). SST anomalies (figure 10, red) increased markedly in late spring and remained elevated through the remainder of 2022.…”
Section: Mediterranean 2022mentioning
confidence: 98%
“…There is general agreement [60][61][62] that the intense warming of the surface layer started early, during May 2022, since by June SSTs (sea surface temperatures, based on satellite data) were already above normal in the western Mediterranean. Martinez et al [10] even compute that the first 2022 severe MHW started by 15 June 2023. Then, in the NW part of the Mediterranean as well as throughout the Mediterranean, the SST has constantly been higher than the climatological baseline until spring 2023 (at least).…”
Section: The Record-breaking 2022 Marine Heatwavementioning
confidence: 99%
“…At the Mediterranean scale, the SST anomalies ranged between 1.5 and 2 • C during the meteorological summer, and until April 2023 all anomalies ranged between 0.5 and 1.5 • C. At the local scale, some SST anomalies higher than 2 • C persisted in the south-western part. In their Mediterranean main MHW catalogue, Martinez et al [10] found two MHW events classified as 'severe' (as in 2003): from 15 June to 21 August 2022 and from 24 October to 22 November 2022. Whatever the domain considered and the criteria applied, this extreme event had a record-breaking duration.…”
Section: The Record-breaking 2022 Marine Heatwavementioning
confidence: 99%
See 1 more Smart Citation